Efficacy of Randu Honey Supplementation on Callus Formation in Closed Fractures of the Tibia in Wistar Rats - Afifurrahman; Wiria Aryanta; Mgs Irsan Saleh (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Tibial fracture is one of the most common injuries. Randu honey has the potential to speed up fracture healing. This study aims to determine the efficacy of randu honey supplementation on callus formation in closed fractures of the tibia in Wistar rats. Methods: This research uses a true experimental design with post test only control group design. A total of 36 Wistar rats were divided into two groups, namely the control group and the treatment group which were given 200g/BW(gram)/day of randu honey. Fractures were made on the rat tibia and callus diameter was measured at 3 weeks after treatment. Results: The callus diameter in the treatment group was significantly larger than the control group (p<0.05) in radiological and macroscopic measurements. Conclusion: Supplementation with randu honey is effective in the formation of callus in closed fractures of the tibia in Wistar rats.